THE USE OF THEMATIC DICTIONARIES AS A MEDIUM FOR EARLY CHILDHOOD LANGUAGE DEVELOPMENT - Saptiani, Saptiani; Mahriza, Rita; Rahmah, Meutia; Fithriani, Fithriani (Bunayya, 2025)
This study uses three-language thematic dictionaries (English, Arabic, and Indonesian) to examine how early childhood language development recognizes foreign vocabulary. Classroom Action Research is applied in this study and is conducted in three cycles, with two sessions per cycle. The study focuses on the child's ability to identify words in the themed dictionary. Fourteen kindergarten students become the subject of the study. Documentation and observation are used in the data-gathering process for this study. Thematic dictionaries are used in the learning process to introduce vocabulary while focusing on each theme through various learning strategies. The study's findings were 33% for cycle I presentations, 75% for cycle II, and 94% for cycle III. Thus, three-language thematic dictionaries (English, Arabic, and Indonesian) can help young children enhance their language skills..